Coordinating success, predicting failure? Why the market vs state debate misses the mark in Asia - Simon Commander; Saul Estrin (Institute of Labor Economics (IZA), 2023)
Much of the debate about Asia's economic success has focussed on the respective roles of the market and state. It has been argued that industrial policy has helped address market failures and achieve critical coordination of development planning and process. Yet, starkly contrasting market and state ignores the way that both have been closely intertwined. Indeed, across the different economic and political systems in Asia, a common feature has emerged in which government and big, diversified and mostly family-owned business groups work in close connection to support their mutual interests. Through such ties, Asia has found a solution to many of the problems of economic development by a different type of coordination. Whilst highly effective in a phase of extensive growth, such connections carry less beneficial consequences. Not least, the accumulation of market power and the restraint of competition that result from preferential ties between business groups and political power. At the same time, the lock-hold of business groups limits growth in the formal economy, in employment whilst also stoking inequality. Further, as Asia searches for greater innovation to drive progress, such close ties are far more likely to stand in the way, deterring new entrants and holding back the creation of more broad-based innovation. Breaking down the entrenched power of connected business groups will require new policies that address head-on the distortions that these connections create. These include measures to deter recourse to the business group format itself.
Keywords: L5; L22; O25; O53; 330; Asia growth; industrial policy; business groups